Validation of instruments used to establish practical experience in high school chemistry - Khoali, Thabo Johannes (My University, 2014)
It is essential for learners to have practical experience as this will equip them with cognitive and manipulative skills, acquisition o f an academic attitude to working. It is the only way of experiencing at first hand many o f the phenomena and events that science addresses. This study aims to establish the validity o f a questionnaire consisting o f three existing instruments used to probe high school students’ chemistry practical experience. Two aspects o f practical experience that are being looked at are: a general practical experience which consists of what students say about their levels o f exposure to experimental work; and specific remembered practical experience. Specific remembered practical experience is established through the extent to which students are able to name and describe the use o f standard laboratory apparatus they have actually used in school practical work. The three instruments have been used in the past to measure students’ practical experience, and though piloted, were never validated. Each instrument was administered in the form o f a questionnaire to Grade 12 students in 4 schools. The 4 schools were selected as a stratified sample. Sixteen students from the 4 schools were interviewed as a follow up. Instrument 1 (the primary instrument) which consisted o f 10 pictures o f common chemistry apparatus was validated using the interview responses. Instrument 1 was then used to validate the other two instruments. Findings show that the instrument 1 was valid overall, but could not establish whether students had teacher demonstrations or not. Some inconsistencies were identified w ith the other two instruments. Therefore, instrument 2 and 3 were found not valid.Some suggestions for the improvement o f instrument 1 are offered.